Flt3L, LIF, and IL‐10 combination promotes the selective in vitro development of ESAMlow cDC2B from murine bone marrow. Issue 12 (14th April 2022) - Cyran, Laura; Serfling, Julia; Kirschner, Luisa; Raifer, Hartmann; Lohoff, Michael; Hermanns, Heike M.; Kerstan, Andreas; Bodem, Jochen; Lutz, Manfred B.
Abstract: The development of two conventional dendritic cells (DC) subsets (cDC1 and cDC2) and the plasmacytoid DC (pDC) in vivo and in cultures of bone marrow (BM) cells is mediated by the growth factor Flt3L. However, little is known about the factors that direct the development of the individual DC subsets. Here, we describe the selective in vitro generation of murine ESAM low CD103 − XCR1 − CD172a + CD11b + cDC2 from BM by treatment with a combination of Flt3L, LIF, and IL‐10 (collectively named as FL10). FL10 promotes common dendritic cell progenitors (CDP) proliferation in the cultures, similar to Flt3L and CDP sorted and cultured in FL10 generate exclusively cDC2. These cDC2 express the transcription factors Irf4, Klf4, and Notch2, and their growth is reduced using BM from Irf4 −/− mice, but the expression of Batf3 and Tcf4 is low. Functionally they respond to TLR3, TLR4, and TLR9 signals by upregulation of the surface maturation markers MHC II, CD80, CD86, and CD40, while they poorly secrete proinflammatory cytokines. Peptide presentation to TCR transgenic OT‐II cells induced proliferation and IFN‐γ production that was similar to GM‐CSF‐generated BM‐DC and higher than Flt3L‐generated DC. Together, our data support that FL10 culture of BM cells selectively promotes CDP‐derived ESAM low cDC2 (cDC2B) development and survival in vitro. Abstract : In vitro culture of murine bone marrow cells in Flt3L + LIF + IL‐10 promotes CD11b + ESAM low cDC2B subset generation from CDP but blocks cDC1 and pDC development. Flt3L alone or combined does not induce cDC2A generation in vitro.